2021 60th IEEE Conference on Decision and Control (CDC) 2021
DOI: 10.1109/cdc45484.2021.9683437
|View full text |Cite
|
Sign up to set email alerts
|

Direct data-driven model-reference control with Lyapunov stability guarantees

Abstract: In this work, we introduce a novel data-driven model-reference control design approach for unknown linear systems with fully measurable state. The proposed control action is composed by a static feedback term and a reference tracking block, which are shaped from data to reproduce the desired behavior in closed-loop. By focusing on the case where the reference model and the plant share the same order, we propose an optimal design procedure with Lyapunov stability guarantees, tailored to handle state measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…, M , where Gi , bi , c d,i and Si indicate the rows of G, b, c d and S associated with the i-th set of active constraint, and GW,i is constructed accordingly. Lastly, by selecting the first element of this sequence, it can easily be shown that the control action to be applied is indeed piecewise affine and that it has the structure in (9), thus concluding the proof.…”
Section: The Rows Of G = Gmentioning
confidence: 69%
See 2 more Smart Citations
“…, M , where Gi , bi , c d,i and Si indicate the rows of G, b, c d and S associated with the i-th set of active constraint, and GW,i is constructed accordingly. Lastly, by selecting the first element of this sequence, it can easily be shown that the control action to be applied is indeed piecewise affine and that it has the structure in (9), thus concluding the proof.…”
Section: The Rows Of G = Gmentioning
confidence: 69%
“…Then, problem (30) is explicitly solved by a piecewise affine law defined as in (9), with χ substituting χ.…”
Section: Handling Changing Set Points In R-eddpcmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, some studies addressing the stability or stabilization criteria from a data-driven point of view, have been published. In particular several problems related to the design of state/output feedback controllers for linear systems have been revisited [5], [6], [18], [19]. In these works considering the case of exact data experiments for linear time-invariant systems, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions can be included directly in the algorithm defined for control design. Alternatively, the behavioural framework in [14] has paved the way to the inclusion of data-dependent Linear Matrix Inequalities (LMIs) for closed-loop stability in several data-driven control problems, e.g., direct data-driven linear quadratic regulator design [15], data-enabled predictive control [16], direct data-driven model-reference control [17], dealing also with noisy data [18], [19]. Also, in the field of nonlinear systems, methods for robust control from data have been provided [20], [21].…”
Section: Introductionmentioning
confidence: 99%